2011
DOI: 10.1097/mop.0b013e32834cd67a
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy for primary immunodeficiency

Abstract: Gene therapy offers a valuable alternative management option for selected immunodeficiency patients who lack a suitable donor for HSCT. Clinical trials have confirmed proof-of-principle in terms of stem cell transduction and subsequent immune reconstitution, but have also highlighted the potential for clonal disturbances related to semi-random vector insertion within the genome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The risk of insertional mutagenesis in slowly turning over differentiated lung epithelium is unknown, but is likely to be lower than in rapidly dividing bone marrow cells. In addition, the improved design of self-inactivating lentiviral vectors has improved safety (21). Here we compared survival, weight, and lung histology during a 24-month study period and did not see any differences between F/HN-SIV-and PBS-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of insertional mutagenesis in slowly turning over differentiated lung epithelium is unknown, but is likely to be lower than in rapidly dividing bone marrow cells. In addition, the improved design of self-inactivating lentiviral vectors has improved safety (21). Here we compared survival, weight, and lung histology during a 24-month study period and did not see any differences between F/HN-SIV-and PBS-treated mice.…”
Section: Discussionmentioning
confidence: 99%
“…25 Unfortunately, inherent risk proved unacceptably high, with mutagenic events detected for SCID-X1, 26 Wiskott-Aldrich syndrome, 27 and XCGD. 28 With a shift toward safer lentiviral vectors designed to self-inactivate, similar adverse events have yet to be observed.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using retroviral gene therapy for X-linked severe combined immunodeficiency patients have found that many patients treated with this retroviral vector developed leukemia [34]. However, newer studies offer more encouraging news: with increased experience and modified conditioning regimens, improved outcomes have been observed without oncogenetic risks after more than a 4-year follow-up of additional immune deficient patients treated with a different retrovirus vector [35]. …”
Section: Factor (F) VIII Biology: Intracellular Processing and Expresmentioning
confidence: 99%